Humoral antibody to Mobiluncus curtisii, a potential serological marker for bacterial vaginosis. - Schwebke, J R (1996)
While bacterial vaginosis (BV) is a polymicrobial syndrome, Mobiluncus spp. are the organisms most highly associated with this condition. It is possible that serum antibody to Mobiluncus spp. could be used as a serological marker for BV. Using immunofluorescence techniques, we studied the prevalence of antibody to M. curtisii among three cohorts-pregnant women, pediatric patients, and sexually inexperienced women. The prevalence of antibody in each of these three groups was 75, 6, and 0%, respectively. Of the three pediatric patients with antibody to Mobiluncus curtisii, two were neonates, and the only class of antibody detected was immunoglobulin G. Among the cohort of pregnant women, the presence of antibody could not be correlated with a clinical history of BV. Serum antibody to M. curtisii could be a useful serological marker for BV. The lack of correlation of antibody positivity to historical information regarding BV suggests that unrecognized or undiagnosed episodes of BV may be common.